Comparison of the Effects of Gonadotropin Releasing Hormone Agonists and Antagonists on Endometrial Development in Women who Had Inadequate Endometrial Development in a Previous Assisted Reproduction Treatment Cycle; A Randomised Parallel Group Pilot Trial - Leylek, Özkan Aydın; Ata, Barış; Api, Murat; İkidağ, Ali; Urman, Bülent (Gynecology Obstetrics & Reproductive Medicine, 2008)
OBJECTIVE: To analyse the effects of GnRH agonist or antagonist administration on endometrium of patients with poor prognostic feasures of endometrium undergoing IVF STUDY DESIGN: A randomised controlled trial was done in 152 women undergoing an assisted reproduction treatment cycle subsequent to an unsuccessful cycle in which they had demonstrated poor endometrial growth. Assited reproduction treatment using standard stimulation protocols were used, implantation, clinical and ongoing pregnancy rates were compared in the two groups. RESULT: A total of 152 patients were included in the trial. 76 women were allocated to stimulation with the long GnRH agonist protocol while 76 women were allocated to stimulation with the flexible GnRH antagonist protocol. The total oocyte number, the number of excellent quality embryos and the number of embryo transfered were not significantly different between the groups. Implantation rate of cetrotide group was higher than leuprolide group which was not statistically significant (24.1% versus 15.3, p=0.068). The clinical and ongoing PRs rates in the cetrotide group were significantly higher than in the leuprolide group (clinical pregnancy rate 55.2% versus 32.8%, p=0.054, ongoing pregnancy rate 44.7% versus 27.6 %, p=0.028, respectively). CONCLUSION: Cetrorelix seems to provide better outcome than leuprolide acetate in IVF cycles with poor endometrial responders.